Comparison of the effects of metformin and empagliflozin on cardiac function in heart failure with preserved ejection fraction mice - Liu, Xiehong; Zhao, Huiqi; Liu, Sisi; Wen, Siao; Fan, Wenjuan; Xie, Qiong; Cui, Bo; Zhou, Lin; Peng, Jianqiang; Pan, Hongwei; Zheng, Zhaofen; Zhang, Qinghai (Frontiers in Cardiovascular Medicine, 2025)
PurposeRecent evidence suggests that empagliflozin (EMPA) and metformin (MET) may improve prognosis in heart failure with preserved ejection fraction (HFpEF) patients. This study aims to compare their effects on cardiac structure and function in HFpEF.MethodsMale C57BL/6J mice were fed a high-fat diet with L-NAME for 8 weeks to induce HFpEF, followed by 4 weeks of MET or EMPA treatment. Cardiac structure and function were assessed. Network pharmacology and bioinformatics identified key targets, validated by RT-qPCR and WB.ResultsEMPA-treated mice lost weight, unlike MET-treated ones. MET reduced systolic blood pressure significantly. Both treatments improved glucose tolerance; MET enhanced insulin sensitivity. EMPA increased exercise tolerance by extending exhaustion distance. Both treatments improved diastolic function, reduced heart weight, and attenuated myocardial fibrosis and hypertrophy. Plasma NT-proBNP levels were slightly elevated but not significant. EMPA downregulated HSP90 mRNA and protein expression; both drugs downregulated TGFβ.ConclusionMET and EMPA improve cardiac fibrosis, diastolic function, and pulmonary congestion in HFpEF mice. MET acts by downregulating TGFβ, while EMPA affects collagen metabolism and downregulates HSP90 and TGFβ. These findings offer insights into HFpEF treatment.